Pertanggungjawaban Pidana terhadap Bidan yang Membantu Menangani Abortus Provocatus Secara Ilegal - I Putu Wahyu Putra Suryawan; I Nyoman Gede Sugiartha; Diah Gayatri Sudibya (Jurnal Interpretasi Hukum, 2021)
Provocatal abortion is the result of expulsion of conception before its time less than 20 weeks which is done deliberately by using drugs or medical devices. Currently, provocatus abortion is rife with adolescents who are involved in promiscuity and adult women who are married. In carrying out the act of abortion provocatus, some are done by themselves using drugs, traditional ingredients or massage, and some are assisted by medical doctors and midwives. that is done illegally. This study aims to determine the legal arrangements governing the act of legally abortion provocatus, and to determine the criminal responsibility of midwives who help treat provocatus abortion legally. This research uses a type of normative legal research, by examining the 1945 Constitution of the Republic of Indonesia, Law No. 36 of 2009 and the Criminal Code as a basis for knowing criminal liability to midwives who help deal with illegal abortion provocatus. The results of this study indicate that the legal arrangements regarding provocatus abortion are legally regulated in Article 75 paragraph (2) of the Health Law, which states that the prohibition on abortion can be lifted if it is carried out on a pregnant woman whose womb experiences symptoms of a medical emergency that endangers her life / fetus being conceived is suffering from genetic diseases or congenital defects that do not allow it to be cured so that it has the potential to make it difficult for the baby to lead a normal life. Then, the criminal liability for a midwife who helps handle provocatus abortion illegally has different sanctions from the criminal responsibility of the main perpetrator (doctor).